The Role of Transformational Leadership, Self Efficacy and Professional Competence on Knowledge Sharing and Lecture Performance - Priyono Budi Santoso; John Tampil Purba; Gracia Shinta S. Ugut; Sidik Budiono (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2020)
The purpose of this study is to analyze the relationship between Transformational Leadership, Self Efficacy and Professional Competence on Knowledge Sharing and Lecture Performance. In this study using quantitative methods and data analysis techniques Structural Equation Modeling (SEM) using SmartPLS 3.0 software. In this study using quantitative methods and data analysis techniques Structural Equation Modeling Equation Modeling using SmartPLS 3.0 software. The sample selection method used non-probability sampling methods. Respondents in this study were private university lecturers in the city of Tangerang. Data collection in this study was conducted using an online questionnaire. Online questionnaires were sent to the respondents as many as 230 questionnaires, the next step is to evaluate the returned questionnaires, namely the questionnaires that returned 220 and did not return totaling 10 questionnaires. Based on the results of data analysis, it is concluded that Transformational Leadership has a significant effect on Lecture Performance, Self Efficacy has a significant effect on Lecture Performance, Professional Competence has no significant effect on Lecture Performance, Knowledge Sharing has no significant effect on Lecture Performance. The novelty of this research is the relationship model of the Role of transformational leadership, self-efficacy and professional competence on knowledge sharing and lecture performance